Actualization of Understanding Children's Education at the Aqil Baligh Stage Based on the Prophet's Hadith for Millennial Muslim Generation in Karang Taruna RW 007, Sukamantri Village - Ainul Azhari; Dul Jalil; Risalatu Zakiah (LP2M of Institute for Research and Community Services - UIN Walisongo, 2024)
Understanding the education of aqil baligh children is one of the important aspects in shaping the character of a good young generation, especially in the context of Islamic teachings. In the fast-paced digital era and globalisation, the challenges in educating the Muslim millennial generation are increasingly complex, especially in understanding and applying the concept of education in accordance with religious teachings. This study aims to actualise an understanding of the education of aqil baligh children based on the hadith of the Prophet Muhammad SAW in the Muslim millennial generation. The approach used is an understanding of hadith literacy relevant to the age of puberty, as well as how to implement these principles in the context of the daily life of the millennial generation today. Through counseling, discussions, and training, this community service programme educates parents, educators, and the general public about the importance of hadith-based education in preparing children to enter adulthood with solid moral, ethical, and faith. The expected results birutoto of this activity are increased public awareness and understanding of the importance of teaching in accordance with Islamic principles in the education of aqil baligh children, as well as the creation of a millennial generation of Muslims who are more qualified, noble, and ready to face the challenges of the times.